Intraperitoneal paclitaxel and cisplatin compared with dose-dense paclitaxel and carboplatin for patients with stage III ovarian cancer. (October 2020) - Murphy, Madison; Martin, Grace; Mahmoudjafari, Zahra; Bivona, Cory; Grauer, Dennis; Henry, David
Introduction: Patients diagnosed with stage III ovarian cancer are at high risk of recurrence and optimal adjuvant therapy is often debated. There is limited literature that directly compares intraperitoneal paclitaxel and cisplatin with dose-dense paclitaxel and carboplatin. Objectives: The primary objective was to compare progression-free survival, overall survival, and tolerability of adjuvant intraperitoneal paclitaxel and cisplatin to dose-dense paclitaxel and carboplatin in stage III ovarian cancer patients. Methods: A retrospective, IRB-approved, single center chart review was conducted reviewing adult patients with stage III ovarian cancer undergoing adjuvant intraperitoneal therapy or dose-dense therapy between 2010 and 2018. Results: Eighty-two patients were included in the final analysis; 44 in the intraperitoneal group and 38 in the dose-dense group. Intraperitoneal therapy was not associated with a longer progression-free survival (35.4 vs. 31.1 months; P = 0.97). The duration of overall survival did not differ between intraperitoneal and dose-dense (56.3 vs. 54.5 months; P = 0.55). Dose reductions were less frequent with intraperitoneal than dose-dense (11.36% vs. 31.58%; P = 0.02). No difference in treatment delays (45.5% vs. 65.8%; P = 0.07), dose cancellations (59.1% vs. 57.9%; P = 0.91), supportive care additions (95.5% vs. 84.2%; P = 0.09), or therapy discontinuation (59.1% vs. 39.5%; P = 0.07) between groups was noted. Conclusions: Intraperitoneal therapy with paclitaxel and cisplatin, as compared with dose-dense paclitaxel and carboplatin, did not prolong progression-free or overall survival in the adjuvant setting among stage III ovarian cancer patients. A trend towards decreased tolerability was noted with intraperitoneal therapy.